2017
DOI: 10.21767/2471-9838.100028
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bacterial Adhesion on Nanoparticle Filler-Reinforced Dental Composites after Different One-Step Finishing Timing Using a Constant-Depth Film Fermenter

Abstract: This in vitro study evaluates the influence of application time of a one-step finishing system has on biofilm accumulation over nanoparticle filler-reinforced dental composites using a microcosm biofilm model in a constant depth film fermenter (CDFF). For that, sixty disk-shaped specimens (ø=5 mm × 2 mm thick) were made with nanoparticle filler reinforced dental composites (EsthetX™ and IPS Empress Direct). The specimens were manually polished with a finishing system (Enhance®) following the manufacturer's ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results of the dynamic caries tooth model indicated that the sealing material containing DMAHDM has intense antibiofilm activity and potential applicability for materials development. In most studies, short periods (48 h) and static multi‐well models are used to study biofilm growth on cationically modified surfaces (Cattò & Cappitelli, 2019; Ganewatta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the dynamic caries tooth model indicated that the sealing material containing DMAHDM has intense antibiofilm activity and potential applicability for materials development. In most studies, short periods (48 h) and static multi‐well models are used to study biofilm growth on cationically modified surfaces (Cattò & Cappitelli, 2019; Ganewatta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%